Fecal microbiota transplantation and short‐chain fatty acids protected against cognitive dysfunction in a rat model of chronic cerebral hypoperfusion - Su, Shao‐Hua; Chen, Ming; Wu, Yi‐Fang; Lin, Qi; Wang, Da‐Peng; Sun, Jun; Hai, Jian (CNS neuroscience & therapeutics, 2023)
Aims Clear roles and mechanisms in explaining gut microbial dysbiosis and microbial metabolites short‐chain fatty acids (SCFAs) alterations in chronic cerebral ischemic pathogenesis have yet to be explored. In this study, we investigated chronic cerebral hypoperfusion (CCH)‐induced gut microbiota and metabolic profiles of SCFAs as well as the effects and mechanisms of fecal microbiota transplantation (FMT) and SCFAs treatment on CCH‐induced hippocampal neuronal injury. Methods Bilateral common carotid artery occlusion (BCCAo) was used to establish the CCH model. Gut microbiota and SCFAs profiles in feces and hippocampus were evaluated by 16S ribosomal RNA sequencing and gas chromatography–mass spectrometry. RNA sequencing analysis was performed in hippocampal tissues. The potential molecular pathways and differential genes were verified through western blot, immunoprecipitation, immunofluorescence, and ELISA. Cognitive function was assessed via the Morris water maze test. Ultrastructures of mitochondria and synapses were tested through a transmission electron microscope. Results Chronic cerebral hypoperfusion induced decreased fecal acetic and propionic acid and reduced hippocampal acetic acid, which were reversed after FMT and SCFAs administration by changing fecal microbial community structure and compositions. Furthermore, in the hippocampus, FMT and SCFAs replenishment exerted anti‐neuroinflammatory effects through inhibiting microglial and astrocytic activation as well as switching microglial phenotype from M1 toward M2. Moreover, FMT and SCFAs treatment alleviated neuronal loss and microglia‐mediated synaptic loss and maintained the normal process of synaptic vesicle fusion and release, resulting in the improvement of synaptic plasticity. In addition, FMT and SCFAs supplement prevented oxidative phosphorylation dysfunction via mitochondrial metabolic reprogramming. The above effects of FMT and SCFAs treatment led to the inhibition of CCH‐induced cognitive impairment. Conclusion Our findings highlight FMT and SCFAs replenishment would be the feasible gut microbiota‐based strategy to mitigate chronic cerebral ischemia‐induced neuronal injury. Fecal microbiota transplantation (FMT) and short‐chain fatty acids (SCFAs) replenishment exerted anti‐neuroinflammatory effects through switching microglial phenotype from M1 toward M2. Furthermore, FMT and SCFAs treatment alleviated neuronal loss and microglia‐mediated synaptic loss and maintained the normal process of synaptic vesicle fusion and release, resulting in the improvement of synaptic plasticity. In addition, FMT and SCFAs supplement prevented oxidative phosphorylation dysfunction via mitochondrial metabolic reprogramming.